UPAYA MENINGKATKAN HASIL BELAJAR MATERI KEWAJIBAN DAN HAKKU MELALUI PENDEKATAN LINGKUNGAN PADA SISWA KELAS III SD NEGERI 93 MALUKU TENGAH - Rivaldo Paul Telussa (Jurnal Cakrawala Ilmiah, 2023)
This research was conducted based on the findings in the field which stated that student learning outcomes were low. This research was conducted with the aim of knowing student learning outcomes through an environmental approach. The location of this research was conducted at SD Negeri 93 Central Maluku, and the subjects in this study were 33 grade III elementary school students. Data collection techniques in this study are using observation and tests, while data analysis techniques are qualitative and quantitative. The research results obtained were that in cycle I it was found that 18 students had completed with a percentage of 54.54% and 15 students who had not completed with a percentage of 45.45%. The average value obtained in the post test results in cycle I was 67.45%. In cycle II there were 31 students who completed with a percentage of 93.93% and 3 students who did not complete with a percentage of 6.06% and the average score obtained in the post test results in cycle II was 86.84%. The conclusion from this study is that using learning using an environmental approach can improve learning outcomes in the subject of my obligations and rights in class III students of SD Negeri 93 Central Maluku.